Genetic variability, general performance and interrelationships of grain yield and its components of nine inbred lines of maize under Striga infested and non-infested soil - Karrar, Sara; Alhussein, Mohammedein; Ibrahim, Abu Elhassan; Ali, Eltahir (Gezira Journal of Agricultural Science, 2013)
Nine inbred lines of maize were evaluated at the Gezira Research Station (GRS), Agricultural Research Corporation (ARC), Wad Medani, Sudan, under Striga non-infested (normal conditions) and infested (stress conditions) soil for seasons 2008 and 2009. A randomized complete block design with three replicates was used. The objective was to estimate the general performance, genetic variability and interrelationships of grain yield and its components. Data were collected on days to 50% tasseling, plant height, ear height, ear length, 100 kernels weight and grain yield. The traits showed significant differences under normal conditions with the exception of ear height in 2008 and grain yield in 2009. Under stress conditions and in 2008, the traits showed no significant differences except for days to tasseling but in 2009, the traits showed significant differences in plant height, ear length and 100 kernel weight. Over seasons, the mean across conditions in grain yield ranged between 425-1181 kg/ha in 2008 and 575-1320 kg/ha in 2009. Line TZSTR148 showed the highest grain yield (1181 kg/ha) as well as early flowering and short plants in 2008, while Line TZSTR133 showed the highest grain yield (1320 kg/ha), early flowering and short plants in 2009. In both seasons under normal and stress conditions, grain yield was highly significantly and positively correlated with plant height, ear height and ear length. Lines TZSTR133 and TZSTR138 were early maturing, short and high yielders and hence were suggested as parents to develop high yielding hybrids after studying their combining ability under conditions of low rainfall environments. However, lines TZSTR148 and 1368STR (tall, late maturing, high yielders) are suggested to develop hybrids for high rainfall zones. تم تقييم تسع سلالات ذرة شامية ذات تربية داخلية مستقدمة في محطة بحوث الجزيرة، هيئة البحوث الزراعية، واد مدني، السودان، تحت ظروف تربة موبوءة وغير موبوءة بالبودة ، خلال موسمين زراعيين متتالين (2008 و2009). ،استخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات لتنفيذ التجربة بهدف تقدير الأداء العام والاختلافات الوراثية وارتباط الصفات بالإنتاجية ومكوناتها.  أخذت بيانات عدد الأيام لظهور 50% من الأزهار المذكرة ، طول النبات، ارتفاع القندول، وزن 100 حبة وإنتاج الحبوب. أظهرت النتائج أن هنالك اختلافاً معنوياً بين السلالات لكل الصفات المدروسة تحت ظروف التربة الغير موبوءة ما عدا ارتفاع القندول في موسم 2008 وإنتاج الحبوب في موسم 2009م. أما تحت ظروف التربة الموبوءة في موسم 2008م كان هنالك اختلافاً غير معنوي بين الصفات الوراثية المدروسة ما عدا عدد الأيام لظهور 50% من الأزهار المذكرة ، بينما أظهرت النتائج في موسم 2009 أن هنالك فروقات معنوية مع طول النبات، طول القندول ووزن الـ 100 حبة. متوسط إنتاج الحبوب في الحالتين تراوح بين 425 – 1181 كيلوجرام/هكتار في موسم 2008 و 575 -1320 كيلو جران /هكتار في موسم 2009م. حققت السلالة TZSTR 148  (مبكرة وقصيرة) أعلى إنتاجية (1181 كيلوجرام/هكتار) في موسم 2008 ، بينما أظهرت السلالة TZSTR 133 (مبكرة وقصيرة) أعلى إنتاجية (1320 كيلوجرام/هكتار) في موسم 2009م. في كلى الموسمين (2008 و2009) وتحت ظروف التربة الموبوءة وغير الموبوءة أظهرت إنتاجية الحبوب ارتباطاً معنوياً وإيجابياً مع طول النبات ارتفاع وطول القندول. السلالتان TZSTR 133و TZSTR 138(قصيرة ومبكرة النضج) لهما إنتاجية عالية لذا يمكن استخدامها في إنتاج الهجن بعد دراسة مقدرتهما للتآلف تحت ظروف الأمطار الخفيفة.  TZSTR 148 و1368STR (طويلة، متأخرة النضج وعالية الإنتاجية) يقترح أن تستخدما في تطوير الهجن في المناطق ذات الأمطار الغزيرة.